Silver-Palm Kernel Expeller Ash Formation by Combustion Technique and its Congo-red Removal Activity - Yudha S, Salprima Yudha S; Nesbah, Nesbah; Mardlia, Zulfikri Achid; Ramadhani, Annisa; Reagen, Muhamad Alvin (Chemistry Department, The University of Brawijaya, 2024)
This study aims to synthesize silver-palm kernel expeller ash (PKE) composites using in-situ combustion at 600 Â°C. Compared to previous methods, the novel in-situ combustion was developed to easily obtain composites in the laboratory using simple procedures. The products obtained were characterized with X-ray diffraction (XRD) analysis. The results showed that the composites contained silver metal peaks and some peaks of a mixture of compounds predicted to be calcium phosphate, calcium hypophosphate, and other undetermined metal oxides. In addition, X-ray fluorescence (XRF) analysis showed the presence of several important minerals derived from PKE combustion. Composites obtained in this study showed better activity as catalysts in the removal of congo-red under sunlight irradiation compared to only PKE ash. Based on these results, the by-products of palm oil processing had the potential to be used for advanced materials preparation.